Creating the optimal workspace for hospital staff using human centred design. Issue 7 (July 2016) - Cawood, T.; Saunders, E.; Drennan, C.; Cross, N.; Nicholl, D.; Kenny, A.; Meates, D.; Laing, R.
Abstract : We were tasked with creating best possible non‐clinical workspace solutions for approximately 450 hospital staff across 11 departments encompassing medical, nursing, allied health, administrative and other support staff. We used a Human‐Centred Design process, involving 'Hear, Create and Deliver' stages. We used observations, contextual enquiry and role‐specific workshops to understand needs, key interactions and drivers of behaviour. Co‐design workshops were then used to explore and prototype‐test concepts for the final design. With extensive employee engagement and design process expertise, an innovative solution was created that focussed on meeting the functional workspace needs of a diverse group of staff requiring a range of different spaces, incorporating space constraints and equity. This project demonstrated the strength of engaging employees in an expert‐led Human‐Centred Design process. We believe this is a successful blueprint process for other institutions to embrace when facing similar workspace design challenges.